Racial and Ethnic Differences in Perceptions of Everyday Discrimination. Issue 4 (October 2017) - Gong, Fang; Xu, Jun; Takeuchi, David T.
This study examines differences in perceptions of discrimination across multiple racial and ethnic minority groups. We focus on structural factors such as race/ethnicity and socioeconomic status (SES) and psychosocial factors such as racial/ethnic identities as predictors of perceived everyday discrimination. Data come from the Collaborative Psychiatric Epidemiology Surveys (CPES), and analyses reveal several important patterns. First, perceived everyday discrimination is highly prevalent among racial/ethnic minorities in the United States and these perceptions largely reflect existing racial/ethnic hierarchies: African Americans and Afro-Caribbeans report the highest level of discrimination, whereas most Asian and Latino groups report less. Second, education, income, and immigration-related factors such as duration of residence and English language proficiency are positively associated with perceived discrimination. Third, the effects of racial/ethnic identity on perceived discrimination vary across ethnic groups, showing stronger associations among Afro-Caribbeans than among other racial and ethnic minorities. Findings from this study help to advance our theoretical understanding and empirical knowledge of racial/ethnic stratification and perceived discrimination in the United States.